Resilience and commitment in nursing students of the Jorge Basadre Grohmann National University in Tacna, Peru 2019 - Yalpa Mojica, Diana (2021)
Objective: To determine the relationship between resilience and commitment in nursing students in Tacna, Peru. Material and methods: Nonexperimental, correlational, cross-sectional study. The population was composed of 179 students from the first to fourth year of the Professional School of Nursing of the Jorge Basadre Grohmann National University in Tacna, during the 2019, who were surveyed with prior informed consent, two validated questionnaires were applied. For the analysis, the Chi square statistic was used, with a 95 % confidence. Results: Of the total number of students, 88.8 % were female; 57 % were 19 to 21 year-old; 60.3 % expressed a high level of commitment and 35.8 % a medium level, being this high commitment by dedication (69.3%), vigor (520%) and absorption (55.3 %). 54.7% showed high level resilience and 44.7 % medium level resilience, with this resilience being high due to personal competence (96.1 %) and optimism (60.3 %); 44.7 % showed high commitment and resilience with a statistically significant association (p<0.01), resilience presented direct association with all dimensions of commitment (dedication, vigor and absorption) and commitment was associated with all dimensions of resilience (personal competence, self-confidence, optimism and relationships) (p<0.05). Conclusion: There is a significant relationship between resilience and commitment in nursing students.